Therapeutic approaches for treating hemophilia A using embryonic stem cells - Shogo Kasuda (Hematology/Oncology and Stem Cell Therapy, 2016)
Hemophilia A is an X-linked rescessive bleeding disorder that results from F8 gene aberrations. Previously, we established embryonic stem (ES) cells (tet-226aa/N6-Ainv18) that secrete human factor VIII (hFVIII) by introducing the human F8 gene in mouse Ainv18 ES cells. Here, we explored the potential of cell transplantation therapy for hemophilia A using the ES cells. Transplant tet-226aa/N6-Ainv18 ES cells were injected into the spleens of severe combined immunodeficiency (SCID) mice, carbon tetrachloride (CCl4)-pretreated wild-type mice, and CCl4-pretreated hemophilia A mice. F8 expression was induced by doxycycline in drinking water, and hFVIII-antigen production was assessed in all cell transplantation experiments. Injecting the ES cells into SCID mice resulted in an enhanced expression of the hFVIII antigen; however, teratoma generation was confirmed in the spleen. Transplantation of ES cells into wild-type mice after CCl4-induced liver injury facilitated survival and engraftment of transplanted cells without teratoma formation, resulting in hFVIII production in the plasma. Although CCl4 was lethal to most hemophilia A mice, therapeutic levels of FVIII activity, as well as the hFVIII antigen, were detected in surviving hemophilia A mice after cell transplantation. Immunolocalization results for hFVIII suggested that transplanted ES cells might be engrafted at the periportal area in the liver. Although the development of a safer induction method for liver regeneration is required, our results suggested the potential for developing an effective ES-cell transplantation therapeutic model for treating hemophilia A in the future. Keywords: Cell therapy, Embryonic stem cell, Hemophilia A, Mouse model